Plastics, Birds, and Humans: Awakening and Quickening Ecological Minds in Young Children and Their Teachers - Parnell, Will; Cullen, Julianne; Domingues, Michelle Angela (Journal of Childhood Studies, 2022)
Working with educators, artists, young children, and materials to make meaning with place affected by human environmental impacts, this study zooms in on a documentary of dying birds who’ve swallowed plastics. The birds’ habitat is an eye-opening 2,000 miles from the nearest continent and is infested with trash and plastic. The birds ingest many shiny plastic bits and slowly die. This research paper focuses in on experiences of sharing this documentary with teacher educators at an international conference, then educators in our own context, and then with early childhood artists working in reuse materials. The research captures a series of dialogues and materials interactions at each of the three gatherings about possible ways to research with young children on daunting ecological issues in perilously turbulent times.